Sensitivity of the Standard Chlamydia trachomatis Culture Method Is Improved After One Additional In Vitro Passage. Issue 5 (14th March 2016) - Shao, Lili; Guo, Yuanli; Jiang, Yong; Liu, Yuanjun; Wang, Mei; You, Cong; Liu, Quanzhong
Abstract : Background: Chlamydia trachomatis causes the most common bacterial sexually transmitted infection (STI) worldwide. Although highly sensitive nucleic acid amplification tests (NAATs) are used to routinely diagnose chlamydial infection, C. trachomatis isolation by cell culture is still preferred for legal cases and epidemiological studies because of its high specificity; however, the sensitivity of traditional two‐passage diagnostic cultures is significantly lower than that of NAATs. Therefore, we sought to analyze if additional in vitro passaging of clinical samples would improve detection sensitivity of C. trachomatis . Methods: Clinical swabs ( n = 428) were collected from Tianjin Medical University General Hospital, grown in McCoy cells for up to five passages, and analyzed for the presence of inclusions by iodine staining. Results were confirmed by routine PCR‐based methods. Results: Viable C. trachomatis organisms were detected in 91 (21.26%) swabs with the traditional two‐passage protocol, which increased to 145 (33.88%) and 149 (34.81%) following three and four passages, respectively. Thus, the standard protocol yielded a false‐negative rate of nearly 39%. Subsequent PCR‐based diagnostics revealed a concordance rate of 80.98% between these two methods without any false negatives. Conclusion: The results of this study support the use of a three‐passage Chlamydia culture procedure to increase the detection sensitivity of this method.